Efficacy of intravitreal bevacizumab combined with pan retinal photocoagulation versus panretinal photocoagulation alone in treatment of proliferative diabetic retinopathy - Sameen, Murtaza (Pak J Med Sci, 2017)
OBJECTIVE: To compare effectiveness of pan-retinal photocoagulation alone versus panretinal photocoagulation combined with intravitreal bevacizumab on visual acuity and central macular thickness in patients presenting with proliferative diabetic retinopathy. METHODS: This Randomized controlled trial was carried out at Armed Forces Institute of ophthalmology, Pakistan from Jan 2016 to Aug 2016. Seventy six eyes of 50 patients having proliferative diabetic retinopathy and diabetic macular edema were included in the study. All the patients were subjected to detailed clinical examination that included Uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), slit lamp examination of anterior and posterior segments. Optical coherence tomography (OCT) and fundus fluorescein angiography (FFA) were carried out and patients were divided in two groups (GP and GI). Three monthly sessions of Pan retinal photocoagulation (PRP) using Pattern Scan Laser (PASCAL) alone was performed in group GP while PRP along with three monthly intravitreal bevacizumab (IVB) was performed in group GI. BCVA and CMT was recorded 04 weeks after the third PRP session in both the groups. RESULTS: Seventy six eyes of 50 patients (38 in each group) were treated with three sessions of PRP alone and PRP with IVB in Group GP and GI respectively. Mean age of the patient in group GP was 57.47± 6.08 years while that in group GI was 55.69 ±6.58. The magnitude of induced change in BCVA was 0.09 ± 0.15 in GP while 0.22 + 0.04 in GI groups while mean induced change in CMT after treatment was 77.44 ± 92.30 um and 117.50 ± 93.82 um in group GP and GI. CONCLUSION: Laser PRP combined with IVB has superior visual and anatomical outcome than PRP alone in patients with combined presentation of PDR and DME.